Antiphospolipid syndrome in HIV infection - Report on four cases and review of literature - (:unkn) unknown (Hogrefe and Huber Publishers, 2001)
The antiphospholipid antibody syndrome (APS) is a thrombophilic syndrome, defined by the presence of elevated antiphospholipid antibody (aPL). The presence of elevated aPL has been described during the course of human immunodeficiency virus (HIV) infection but has not been commonly associated with thrombosis. Herein, we briefly describe four HIV-infected patients, two children and two adults, with vascular manifestations suggestive of the APS and elevated aPL. In addition, we reviewed the literature regarding APS and APS in the context of HIV infection.